Information asymmetries in the hiring process and the risk of new leader dismissal: insights from English premier league soccer organizations - Desai, Malay N.; Lockett, Andrew; Paton, David (Wiley, 2018)
Why are some new leaders dismissed quicker than others? Adopting agency theory logic we examine how different succession contexts shape boards’ information asymmetries about a potential candidate’s competencies in the hiring process, which influences the propensity of making poor hiring decisions and hence the risk of new leader dismissal. Employing duration analysis on a sample of 164 newly appointed leaders in the English premier league (1996 –2014), we find that the risk of new leader dismissal is: (i) greater when the predecessor leader’s exit was initiated by them rather than by the board; (ii) greater when following a longer tenured predecessor; and (iii) lower for outside successions as compared to inside successions.